Gendered patterns of academic writing strategy use in undergraduate EFL thesis writing - Wynneke Putri Shabirah; Albina Volkotrubova; Satarova Zamira Kalykovna (Researcher and Lecturer Society, 2026)
Academic writing strategies play a crucial role in supporting undergraduate EFL students during thesis writing; however, gender-based differences in strategy use remain underexplored. This study examines gender differences in academic writing strategies employed by undergraduate EFL students when completing their thesis, drawing on Oxford’s Language Learning Strategies framework. Using a quantitative descriptive design, data were collected from 44 undergraduate students (21 male and 23 female) in the Department of English Language and Literature at Universitas Negeri Padang. A 42-item questionnaire was administered to assess six categories of academic writing strategies: memory, cognitive, compensation, metacognitive, affective, and social. The results indicate that while both male and female students employed all six categories, distinct gender-related patterns emerged. Female students reported using metacognitive and affective strategies more frequently, reflecting stronger engagement in planning, monitoring, evaluation, and emotional regulation during thesis writing. Male students, in contrast, demonstrated slightly greater reliance on social strategies, particularly in seeking feedback and external support. No substantial gender differences were observed in memory and compensation strategies. These findings suggest that gender influences how EFL students regulate and support their academic writing during thesis completion. The study highlights the importance of incorporating gender-sensitive approaches in academic writing instruction and thesis supervision to better accommodate students’ strategic preferences.